Intravesical Bacillus Calmette‐Guérin versus mitomycin C for Ta and T1 bladder cancer - Hahne, Stefanie; Kunath, Frank; Coles, Bernadette; Draeger, Desiree Louise; Krabbe, Laura-Maria; Dersch, Rick; Kilian, Samuel; Jensen, Katrin; Dahm, Philipp; Meerpohl, Joerg J. (The Cochrane database of systematic reviews, 2020)
People with urothelial carcinoma of the bladder are at risk for recurrence and progression following transurethral resection of a bladder tumour (TURBT). Mitomycin C (MMC) and Bacillus Calmette‐Guérin (BCG) are commonly used, competing forms of intravesical therapy for intermediate‐ or high‐risk non‐muscle invasive (Ta and T1) urothelial bladder cancer but their relative merits are somewhat uncertain.